Efficient Organic Carbon Burial by Bottom Currents in the Ocean: A Potential Role in Climate Modulation - Shaoru Yin; F. Javier Hernández‐Molina; Weijia Fan; Jiabiao Li (Geophysical Research Letters)
Abstract Bottom currents play a major role in deep‐sea sedimentation, but their significance in the burial of organic carbon is poorly quantified at a global scale. Here we show that Holocene fluxes of organic carbon into the contourite drifts are high, with a global average of 0.09 g cm−2 Kyr−1. At individual drift sites, fluxes are commonly 1–2 orders of magnitude greater than rates in surrounding areas and in global depth‐similar zones. These high fluxes of organic carbon into the contourite drifts are due to high rates of sedimentation. Over the past 50 million years, sedimentation rates at the studied contourite drift sites have overall increased, coincident with decreasing atmospheric CO2 and a cooling global climate. Our work suggests that a ramp‐up of the bottom‐current carbon pump has accelerated removal of CO2 from the atmosphere and oceanic water, thus contributing to the overall global cooling after the Eocene Thermal Maximum.